Effect of Group-Based Rehabilitation Combining Action Observation with Physiotherapy on Freezing of Gait in Parkinson’s Disease - Elisa Pelosin; Roberta Barella; Cristina Bet; Elisabetta Magioncalda; Martina Putzolu; Francesca Di Biasio; Cecilia Cerulli; Mauro Casaleggio; Giovanni Abbruzzese; Laura Avanzino (Neural Plasticity)
Freezing of gait (FoG) is among the most disabling symptoms of Parkinson’s disease (PD) patients. Recent studies showed that action observation training (AOT) with repetitive practice of the observed actions represents a strategy to induce longer-lasting effects compared with standard physiotherapy. We investigated whether AOT may improve FoG and mobility in PD, when AOT is applied in a group-based setting. Sixty-four participants with PD and FoG were assigned to the experimental (AO) or control groups and underwent a 45-minute training session, twice a week, for 5 weeks. AOT consisted in physical training combined with action observation whereas the control group executed the same physical training combined with landscape-videos observation. Outcome measures (FoG questionnaire, Timed Up and Go test, 10-meter walking test, and Berg balance scale) were evaluated before training, at the end of training, and 4 weeks later (FU-4w). Both groups showed positive changes in all outcome measures at posttraining assessment. Improvements in FoG questionnaire, Timed Up and Go test, and Berg balance scale were retained at FU-4w evaluation only in the AOT group. AOT group-based training is feasible and effective on FoG and motor performance in PD patients and may be introduced as an adjunctive option in PD rehabilitation program.